Innovative Solutions for Manufacturing High-Quality Rails in Ukraine - Medovar, L.B.; Stovpchenko, G.P.; Polishko, G.O.; Sybir, A.V.; Kolomiets, D.V.; Kostetsky, Yu.V. (Science and Innovation, 2024)
Introduction. The development of railway transport is a necessary factor in the national development and European integration of Ukraine. Problem Statement. Nowadays, over 80% of rail tracks in the national railway do not meet the requirements for bearing high-speed and heavy-load trains and require replacement. At present, Ukrainian Railways corporation buys rails in foreign countries, which requires significant foreign exchange costs, and therefore the manufacture of high-quality mainstream and switch point rails in our country becomes an urgent need. Purpose. To develop innovative options for organizing the production of premium rails in Ukraine. Materials and Methods. Rail steel. Experimental melting and metallographic studies (using the optical and electron microscopy methods). Results. A high homogeneity (high purity of boundaries and dispersion of primary grains, small inter-lamellar distance of perlite), enhanced properties of the rail metal ensured by conventional electroslag remelting (ESR), and similar characteristic of ingot steel produced by ESR in the current-supplying mold with twice as fast speed of formation have been experimentally proved. Experiments with high-speed ESR and test of fluoride slag in the mold on real continuous casting machine has created the technological framework for a hybrid process of continuous casting with electroslag heating of the meniscus in current-supplying mold (CC + ESR). Conclusions. ESR enables to reduce the minimum hump speed for casting, to improve the density and uniformity of the metal of the axial zone, and to maintain a high quality of the ingot surface. Promising options of technological schemes of waste rail ESR for obtaining the billets with cross-section close to the rail profile have been developed and proposed. Using several modern ESR furnaces with special design will enable to satisfy needs of Ukrainian Railways corporation in highquality mainstream and switch point rails.